Formation of Photoluminescent Lead Bromide Nanoparticles on Aluminoborosilicate Glass - Ruivo, Andreia
A multicomponent aluminoborosilicate photoluminescent glass was synthesized by introducing Pb(II) and NaBr in its composition. The room-temperature photoluminescence is due to the existence of 4 nm nanocrystals, shown using TEM imaging and XRD analysis, which are assigned to PbBr2 nanocrystals. The glasses display a broad emission band with a peak at 2.85 eV by exciting at 3.35 eV, with an anisotropy equal to 0.19 at room temperature. At 77 K, the emission intensity increases 1 order of magnitude and a vibronic structure appears, indicating an electron-phonon coupling with the glass matrix. Time-resolved luminescence measurements of these nanocrystals reveal mixed-order kinetics, with second-order recombination of self-trapped electron centers and a first-order temperature-dependent nonradiative rate constant connected with pathways due to confinement of self-trapped centers.